Antonio da Borgonuovo. L'ascesa di un notaio a Trento fra Trecento e Quattrocento - MALFATTI, STEFANO (Premio Ricerca «Città di Firenze», 2018)
This volume reconstructs the professional biography of a notary from Trento named Antonio di Bartolasio da Borgonuovo between the end of the 14th century and the first decades of the 15th century. The volume retraces his social ascent, with his entrance in Trento's ruling class of the early 15th century and the advantageous marriages of his daughters with members of the powerful Calepini family, as well as his professional ascent, which would lead him to work for the most important institutions of the city (from the Episcopate to the Municipality of Trento) and to be the trusted notary of the Cathedral Chapter for over forty years. His biography and his modus operandi constitute, given the quality and quantity of the documentation he produced, a significant case study to draw a picture of the late medieval notaries in Trento.